Augmented supraspinal fatigue following constant‐load cycling in the heat. (June 2015) - Goodall, S.; Charlton, K.; Hignett, C.; Prichard, J.; Barwood, M.; Howatson, G.; Thomas, K.
Abstract : The development of central fatigue is prominent following exercise‐induced hyperthermia, but the contribution of supraspinal fatigue is not well understood. Seven endurance‐trained cyclists (mean ± SD peak O2 uptake, 62.0 ± 5.6 mL/kg/min) completed two high‐intensity constant‐load cycling trials (296 ± 34 W) to the limit of tolerance in a hot (34 °C, 20% relative humidity) and, on a separate occasion, for the same duration, a control condition (18 °C, 20% relative humidity). Core body temperature (Tc ) was measured throughout. Before and immediately after each trial, twitch responses to supramaximal femoral nerve and transcranial magnetic stimulation were obtained from the knee extensors to assess neuromuscular and corticospinal function, respectively. Exercise time was 11.4 ± 2.6 min. Peak Tc was higher in the hot compared with control (38.36 ± 0.43 °C vs 37.86 ± 0.36 °C; P  = 0.035). Post‐exercise reductions in maximal voluntary contraction force (13 ± 9% vs 9 ± 5%), potentiated twitch force (16 ± 12% vs 21 ± 13%) and voluntary activation (9 ± 7% vs 7 ± 7%) were similar in hot and control trials, respectively. However, cortical voluntary activation declined more in the hot compared with the control (8 ± 3% vs 3 ± 2%; P  = 0.001). Exercise‐induced hyperthermia elicits significant central fatigue of which a large portion can be attributed to supraspinal fatigue. These data indicate that performance decrements in the heat might initially originate in the brain.